Rhophilin-2 Upregulates Glutamine Synthetase by Stabilizing c-Myc Protein and Confers Resistance to Glutamine Deprivation in Lung Cancer - Xiao, Dakai; He, Jiaxi; Guo, Zhihua; He, Huiming; Yang, Shengli; Huang, Liyan; Pan, Hui; He, Jianxing (Frontiers in Oncology, 2021)
Introduction RHPN2, a member of rhophilin family of rho-binding proteins, regulates actin cytoskeleton and vesicular trafficking, and promotes mesenchymal transformation in cancer. We have found that RHPN2 was significantly mutated in lung adenocarcinoma (LUAD). However, the role of RHPN2 in lung cancer is not fully understood. Methods In the present study, we investigated the expression of RHPN2 in 125 patients with LUAD by qRT-PCR and correlated its expression with clinical characteristics. The effects of RHPN2 on the proliferation and invasion of lung cancer cells were determined by CCK-8 and in vitro transwell assays, clonogenic assay, and xenograft mouse model. The RhoA pull down assay and Western blotting were performed to elucidate the mechanism of RNPN2 in tumorigenesis of lung cancer. Results RHPN2 was overexpressed in tumors from LUAD, and high levels of RHPN2 were associated with poor prognosis of LUAD patients. RHPN2 was required for proliferation and invasion of lung cancer cells. Intriguingly, overexpression of RHPN2 conferred the resistance to glutamine depletion in lung cancer cells. Mechanistic studies revealed that ectopic overexpression of RHPN2 promoted the stability of c-Myc protein via phosphorylation at Ser62 and increased c-Myc target glutamine synthetase (GS). Analysis of GS expression in clinical sample showed that the expression of GS was elevated in tumor cells. Kaplan-Meier analysis revealed that high levels of GS were significantly associated with worse overall survival time of the patients with LUAD. Conclusions Taken together, this study suggested that RHPN2 was involved in tumorigenesis of lung cancer via modulating c-Myc stability and the expression of its target GS in lung adenocarcinoma, which links RHPN2 and glutamine metabolism.